Safety of l‐tryptophan produced using Escherichia coli CGMCC 11674 for all animal species. (10th June 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on l ‐tryptophan produced by fermentation with Escherichia coli CGMCC 11674 when used as a nutritional additive in feed and water for drinking for all animal species and categories. The FEEDAP Panel issued an opinion in 2019 in which they could not conclude on the safety of the additive for the target animals and for the consumer due to tryptophan‐related impurities such as 1, 1′‐ethylidene‐bis‐l ‐tryptophan (EBT). The applicant submitted additional data and the European Commission (EC) has requested EFSA to deliver a new opinion on the safety of the additive under assessment. The manufacturing process has been adjusted to reduce the amount of tryptophan‐related impurities and the analysis of three new batches of the additive indicated that levels of EBT and 1‐methyl‐1, 2, 3, 4‐tetrahydro‐β‐carboline‐3‐carboxylic acid (MTCA) represent no safety concerns for the target species or for the consumer.